Design of A 3-5 um and 8-12 um two-color InGaN/AlGaN quantum well infrared photo-detector - Yang, Yuhui (Nanyang Technological University, 2022)
Thermal imaging technology is the cornerstone of military and civil technology. Two-color infrared photodetectors working in mid-wavelength infrared (MWIR, 3 μm-5 μm) and long-wavelength infrared (LWIR, 8 μm-12 μm) band receive significant attention. The excellent optoelectronic and physicochemical properties make it possible for group-III nitride quantum well to fabricate two-color infrared photodetector. However, the component and well width of group-III nitride that can accomplish the two-color detection have not been investigated. In this case, this project utilizes the 8-band model, firstly calculates the transition energy from E1 to E2 and therefore finds the desired component and well width; secondly, these parameters are optimized according to Q_TE curves and Q_TM curves. Finally, Al0.1Ga0.9N/In0.3Ga0.7N (with well width 31 Å and 60 Å) is determined to be the optimal quantum wells.